A toughened PTCR ceramic material and preparation method thereof
By adding alumina whiskers, tetrabutyl titanate and glycerol to the PTCR ceramic material, and performing dry press molding and sintering, the problem of PTCR ceramic material being easily fragile during the air-pressure tightening process is solved, significantly improving the flexural strength and safety of the material.
Patent Information
- Application Number
- CN202411944828.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-04
AI Technical Summary
PTCR ceramic materials are prone to fragmentation during the air pressure tightening process, resulting in poor insulation pressure resistance. Especially in the application of new energy vehicle heaters, it is prone to high-pressure burning, which poses serious safety hazards.
By adding alumina whiskers, tetrabutyl titanate and glycerol to the PTCR ceramic granulation powder, and performing dry molding and sintering, the flexural strength of the material is significantly improved.
This method did not significantly worsen the PTC characteristics of PTCR material, but its flexural strength increased significantly by more than 30%, improving the mechanical properties and safety of the material.
Smart Images

Figure CN119751050A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ceramic materials, and in particular relates to a toughened PTCR ceramic material and a preparation method thereof. Background Art
[0002] PTCR ceramics generally refer to thermistor materials or components with a positive temperature coefficient of resistance (Positive Temperature Coefficient of Resistance). Typical PTCR ceramic materials are semiconductor ceramic materials based on barium titanate, and their characteristics are that when the ambient temperature rises to a certain point (Curie point or switching temperature point), their resistance value will surge by several orders of magnitude. When this material is used as a heating element, its heating power hardly changes with the change of the applied voltage, so it has the function of automatic constant temperature. At the same time, it is widely used in industrial and military electronic equipment, as well as household appliances, because of its simple component structure, low cost, energy saving, no open flames, safety and reliability, and a series of advantages.
[0003] In the application field of heaters, PTCR ceramics need to be processed into heaters through a series of processes such as pneumatic fastening (or extrusion) with electrode strips, aluminum tubes, etc. However, PTCR ceramics are naturally brittle and easily broken when fastened by pneumatic pressure. The debris sometimes pierces the insulating film and causes poor insulation withstand voltage. What is particularly serious is that the debris with electrodes will shorten the distance between the positive and negative electrodes, resulting in high-voltage burning. Especially in the application field of new energy vehicle heaters, due to the high operating voltage and the constant vibration environment, the debris will move and cause the heater to burn, posing a serious safety hazard.
[0004] Therefore, it is necessary and urgent to research and develop an enhanced PTCR ceramic material that has a series of basic properties of PTCR for new energy vehicles such as high voltage resistance, as well as high flexural strength and toughness, in view of the current explosive demand for new energy vehicles. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides a toughened PTCR ceramic material and a preparation method thereof. After adding alumina whiskers, tetrabutyl titanate and glycerol to the PTCR ceramic granulated powder, after dry pressing and sintering, the PTCR properties of the material do not deteriorate significantly, but its flexural strength increases significantly by more than 30%.
[0006] The first object of the present invention is to provide a toughened PTCR ceramic material. The raw material components and their weight parts of the toughened PTCR ceramic material are: 100 parts of PTCR ceramic granulated powder, 0.03-3 parts of alumina whiskers, 0.03-3 parts of tetrabutyl titanate and 0.05-5 parts of glycerol.
[0007] Furthermore, the mass fraction of the aluminum oxide whisker can be 0.03 parts, 0.5 parts, 1 parts, 1.5 parts, 2 parts, 2.5 parts, 3 parts, etc.;
[0008] The mass proportion of tetrabutyl titanate can be 0.03 parts, 0.5 parts, 1 parts, 1.5 parts, 2 parts, 2.5 parts, 3 parts, etc.;
[0009] The mass parts of the glycerol can be 0.03 parts, 0.5 parts, 1 parts, 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts, 4.5 parts, 5 parts, etc.
[0010] In one embodiment of the present invention, the Tc temperature of the PTCR ceramic granulated powder is 120° C.-290° C., the powder particle size is 5 μm-100 μm, and the moisture content is 0.05%-0.3%. Under these conditions, no abnormality occurs during subsequent dry pressing.
[0011] Further, the Tc temperature of the PTCR ceramic granulation powder is 120°C, 125°C, 130°C, 135°C, 140°C, 145°C, 150°C, 155°C, 160°C, 165°C, 170°C, 175°C, 180°C, 185°C, 190°C, 195°C, 200°C, 205°C, 210°C, 215°C, 220°C, 225°C, 230°C, 235°C, 240°C, 245°C, 250°C, 255°C, 260°C, 265°C, 270°C, 275°C, 280°C, 285°C, 290°C, or any Tc temperature between any two values; the powder particle size is 5μm-100μm, 5μm-90μm, 5μm-80μm, 5μm-70μm, 5μm-60μm, 5μm-50μm, 5μm-40μm, 5μm-30μm, 5μm-20μm, 5μm-10μm, 5μm, 10μm, 15μm, 20μm, 25μm, 30μm, 35μm, 40μm, 45μm, 50μm, 55μm, 60μm, 65μm, 70μm, 75μm, 80μm, 85μm, 90μm, 95μm, 100μm, or any size between any two values; moisture content is 0.05%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, or any moisture content between any two values.
[0012] In one embodiment of the present invention, the PTCR ceramic granulated powder further includes 0.3%-1.2% by weight of polyvinyl alcohol.
[0013] Furthermore, the mass proportion of polyvinyl alcohol in the PTCR ceramic granulation powder is 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, or any mass proportion between any two values.
[0014] In one embodiment of the present invention, the diameter of the aluminum oxide whisker is 0.1 μm-5 μm, and the length is 5 μm-100 μm.
[0015] Furthermore, the diameter of the aluminum oxide whisker is 0.1 μm-5 μm, 0.1 μm-4 μm, 0.1 μm-3 μm, 0.1 μm-2 μm, 0.1 μm-1 μm, 0.1 μm, 2 μm, 3 μm, 4 μm, 5 μm, or any diameter between any two values; the length is 5 μm-100 μm, 5 μm-90 μm, 5 μm-80 μm, 5 μm-70 μm, 5 μm-60 μm, 5 μm- 50μm, 5μm-40μm, 5μm-30μm, 5μm-20μm, 5μm-10μm, 5μm, 10μm, 15μm, 20μm, 25μm, 30μm, 35μm, 40μm, 45μm, 50μm, 55μm, 60μm, 65μm, 70μm, 75μm, 80μm, 85μm, 90μm, 95μm, 100μm, or any length between any two values.
[0016] In one embodiment of the present invention, the purity of the aluminum oxide whiskers is above 99.5%.
[0017] In one embodiment of the present invention, the mass ratio of the aluminum oxide whiskers, tetrabutyl titanate and glycerol is 3:5:5.
[0018] The second object of the present invention is to provide a method for preparing the toughened PTCR ceramic material, comprising the following steps:
[0019] S1, dispersing alumina whiskers, tetrabutyl titanate and glycerol uniformly, and then adding PTCR ceramic granulation powder and mixing uniformly to obtain a mixed material;
[0020] S2. Dry-pressing and sintering the mixed material described in S1 to obtain the toughened PTCR ceramic material.
[0021] In one embodiment of the present invention, in S1, the time for uniform dispersion is 15 min-30 min.
[0022] Further, in S1, the time for uniform dispersion is 15 min, 16 min, 17 min, 18 min, 19 min, 20 min, 21 min, 22 min, 23 min, 24 min, 25 min, 26 min, 27 min, 28 min, 29 min, 30 min, or any time between any two values.
[0023] In one embodiment of the present invention, in S1, the uniform mixing speed is 55 rpm-65 rpm, and the time is 0.1 h-8 h.
[0024] Further, in S1, the rotation speed for uniform mixing is 55rpm, 56rpm, 57rpm, 58rpm, 59rpm, 60rpm, 61rpm, 62rpm, 63rpm, 64rpm, 65rpm, or any rotation speed between any two values; the time is 0.1h, 0.5h, 1h, 1.5h, 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, 5.5h, 6h, 6.5h, 7h, 7.5h, 8h, or any time between any two values.
[0025] In one embodiment of the present invention, in S1, the uniform mixing is performed in a V-type mixer or other mixing machine without grinding media, so that the aluminum oxide whiskers are uniformly dispersed in the PTCR ceramic granulated powder without changing their morphology.
[0026] In one embodiment of the present invention, in S2, the dry pressing method is to perform dry pressing in a steel mold and then perform cold isostatic pressing.
[0027] In one embodiment of the present invention, in S2, the sintering temperature is 1250°C-1350°C, the time is 0.1h-1h, the atmosphere is air atmosphere, and the pressure is normal pressure.
[0028] Further, in S2, the sintering temperature is 1250℃, 1255℃, 1260℃, 1265℃, 1270℃, 1275℃, 1280℃, 1285℃, 1290℃, 1295℃, 1300℃, 1305℃, 1310℃, 1315℃, 1320℃, 1325℃, 1330℃, 1335℃, 1340℃, 1345℃, 1350℃, or any temperature between any two values; the time is 0.1h, 0.2h, 0.3h, 0.4h, 0.5h, 0.6h, 0.7h, 0.8h, 0.9h, 1h, or any time between any two values.
[0029] In one embodiment of the present invention, the alumina whisker is a fiber grown in the form of a single crystal, which has a very small diameter and does not contain defects (grain boundaries, dislocations, holes, etc.) that exist in ordinary materials. Its atomic arrangement is highly ordered, so its strength is close to the theoretical value of a complete crystal, and its mechanical strength is equal to the adjacent atomic force; it also has good chemical stability, can be used in an acidic environment, an oxidizing atmosphere, a reducing atmosphere and vacuum conditions, and has a certain corrosion resistance to an alkaline environment, so during high-temperature sintering, the ceramic body material has little erosion on it. Therefore, alumina whiskers are added to the PTCR ceramic material to form a liquid phase at high temperature to promote ceramic sintering. Even if a small amount of alumina whiskers are corroded, the performance of the PTCR material will not fluctuate greatly. Tetrabutyl titanate can wrap the alumina whiskers and prevent the alumina whiskers from reacting with the PTCR ceramic granulation powder during the sintering process. In addition, butyl titanate decomposes into titanium dioxide at high temperature, and titanium dioxide itself is the main raw material of ceramics. Its added part forms the main crystal phase, and part of it forms a glass phase with silicon dioxide in the ceramic component, which can significantly improve the performance of the PTCR ceramic material.
[0030] The technical solution of the present invention has the following advantages compared with the prior art:
[0031] (1) The toughened PTCR ceramic material described in the present invention does not significantly change its PTC characteristics after adding materials such as alumina whiskers. This is because the timing of adding alumina whiskers is different from the conventional addition. It is added after the ceramic powder has been subjected to a series of powder processing processes such as crushing, ball milling, granulation, etc., and then mixed with dry powder without ball milling media to ensure that the morphology of the alumina whiskers does not change significantly (such as whisker breakage, etc.). Therefore, the whiskers can be clearly observed in the sintered ceramics, and the flexural strength of the material is improved. In addition, tetrabutyl titanate can wrap alumina whiskers and prevent alumina whiskers from reacting with PTCR ceramic granulation powder during the sintering process. Butyl titanate also decomposes into titanium dioxide at high temperatures, and titanium dioxide itself is the main raw material of ceramics. Its added part forms the main crystalline phase, and part of it forms a glass phase with silicon dioxide and other ceramic components, which can significantly improve the performance of PTCR ceramic materials.
[0032] (2) The toughened PTCR ceramic material of the present invention has excellent voltage resistance and mechanical strength, and can be used in the thermal management system of new energy vehicles for battery heating or air conditioning heating, and has the characteristics of long service life, safety and reliability. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] In order to make the content of the present invention more clearly understood, the present invention is further described in detail below according to specific embodiments of the present invention in conjunction with the accompanying drawings, wherein:
[0034] Figure 1This is a microstructure photograph of Test Example 1 of the present invention;
[0035] Figure 2 This is a resistance-temperature characteristic comparison curve of test example 2 of the present invention. DETAILED DESCRIPTION
[0036] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. It should be understood that the specific embodiments are only used to explain the present invention, but the embodiments are not intended to limit the present invention.
[0037] In the present invention, unless otherwise specified, technical and scientific terms used in the specification of the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0038] In the present invention, unless otherwise stated, the term "and / or" used in the specification of the present invention includes any and all combinations of one or more related listed items.
[0039] In the present invention, unless otherwise stated, when the terms "comprise" and / or "include" are used in the specification of the present invention, it indicates the existence of the described features, integers, steps, operations, raw materials or components, but does not exclude the existence or addition of one or more other features, integers, steps, operations, raw materials, components or their combinations.
[0040] In the present invention, unless otherwise stated, the experimental methods used in the embodiments of the present invention are conventional methods unless otherwise stated, and the materials, reagents, etc. used are all commercially available unless otherwise stated.
[0041] In the present invention, unless otherwise specified, the aluminum oxide whiskers used in the embodiments of the present invention have a purity of 99.9%, a diameter of 0.1 μm-5 μm, and a length of 5 μm-100 μm.
[0042] Example 1 (Tc185-03)
[0043] The raw material components and their weight parts of the toughened PTCR ceramic material of this embodiment are: 100 parts of PTCR ceramic granulated powder, 0.03 parts of alumina whiskers, 0.03 parts of tetrabutyl titanate and 0.05 parts of glycerol;
[0044] The PTCR ceramic granulation powder has a Tc temperature of 185°C, a powder particle size of 5μm-100μm, a moisture content of 0.15%, and includes polyvinyl alcohol accounting for 0.7% by mass;
[0045] The preparation of toughened PTCR ceramic material specifically includes the following steps:
[0046] S1. Add alumina whiskers, tetrabutyl titanate and glycerol into a 200 mL cylindrical nylon barrel by a V-type mixer, add PTCR ceramic granulation powder after ultrasonic dispersion for 20 min, seal and mix at a speed of 60 rpm for 1.5 h in a V-type mixer without grinding media to obtain a mixture;
[0047] S2. The mixed material is dry-pressed into a ceramic body of 28.0 mm × 17.5 mm × 3.6 mm, and then sintered at 1450° C. for 1 h in an air atmosphere and normal pressure conditions, and then ground into a toughened PTCR ceramic material of 24 mm × 15 mm × 3.0 mm.
[0048] Example 2 (Tc185-15)
[0049] The method is basically the same as Example 1, except that: the raw material components of the toughened PTCR ceramic material and their weight parts are: 100 parts of PTCR ceramic granulated powder, 0.15 parts of alumina whiskers, 0.15 parts of tetrabutyl titanate and 0.25 parts of glycerol;
[0050] The PTCR ceramic granulation powder has a Tc temperature of 185°C, a powder particle size of 5μm-100μm, a moisture content of 0.15%, and includes polyvinyl alcohol accounting for 0.7% by mass.
[0051] Example 3 (Tc185-25)
[0052] The method is basically the same as Example 1, except that: the raw material components of the toughened PTCR ceramic material and their weight parts are: 100 parts of PTCR ceramic granulated powder, 0.25 parts of alumina whiskers, 0.25 parts of tetrabutyl titanate and 0.42 parts of glycerol;
[0053] The PTCR ceramic granulation powder has a Tc temperature of 185°C, a powder particle size of 5μm-100μm, a moisture content of 0.15%, and includes polyvinyl alcohol accounting for 0.7% by mass.
[0054] Comparative Example 1 (Tc185-0-1)
[0055] The method is basically the same as Example 2, except that: the raw material components of the toughened PTCR ceramic material and their weight parts are: 100 parts of PTCR ceramic granulated powder, 0 parts of alumina whiskers, 0.15 parts of tetrabutyl titanate and 0.25 parts of glycerol;
[0056] The PTCR ceramic granulation powder has a Tc temperature of 185°C, a powder particle size of 5μm-100μm, a moisture content of 0.15%, and includes polyvinyl alcohol accounting for 0.7% by mass.
[0057] Comparative Example 2 (Tc185-0-2)
[0058] The method is basically the same as Example 2, except that: the raw material components of the toughened PTCR ceramic material and their weight parts are: 100 parts of PTCR ceramic granulated powder, 0.15 parts of alumina whiskers, 0 parts of tetrabutyl titanate and 0.25 parts of glycerol;
[0059] The PTCR ceramic granulation powder has a Tc temperature of 185°C, a powder particle size of 5μm-100μm, a moisture content of 0.15%, and includes polyvinyl alcohol accounting for 0.7% by mass.
[0060] Comparative Example 3 (Tc185-0-3)
[0061] The method is basically the same as Example 2, except that: the raw material components of the toughened PTCR ceramic material and their weight parts are: 100 parts of PTCR ceramic granulated powder, 0.15 parts of alumina whiskers, 0.15 parts of tetrabutyl titanate and 0 parts of glycerol;
[0062] The PTCR ceramic granulation powder has a Tc temperature of 185°C, a powder particle size of 5μm-100μm, a moisture content of 0.15%, and includes polyvinyl alcohol accounting for 0.7% by mass.
[0063] Example 4 (Tc235-03)
[0064] The method is basically the same as Example 1, except that: the raw material components of the toughened PTCR ceramic material and their weight parts are: 100 parts of PTCR ceramic granulated powder, 0.03 parts of alumina whiskers, 0.03 parts of tetrabutyl titanate and 0.05 parts of glycerol;
[0065] The PTCR ceramic granulation powder has a Tc temperature of 235°C, a powder particle size of 5μm-100μm, a moisture content of 0.16%, and includes polyvinyl alcohol accounting for 0.75% by mass.
[0066] Example 5 (Tc235-15)
[0067] The method is basically the same as Example 4, except that: the raw material components of the toughened PTCR ceramic material and their weight parts are: 100 parts of PTCR ceramic granulated powder, 0.15 parts of alumina whiskers, 0.15 parts of tetrabutyl titanate and 0.25 parts of glycerol;
[0068] The PTCR ceramic granulation powder has a Tc temperature of 235°C, a powder particle size of 5μm-100μm, a moisture content of 0.16%, and includes polyvinyl alcohol accounting for 0.75% by mass.
[0069] Example 6 (Tc235-30)
[0070] The same as Example 4, except that: the raw material components of the toughened PTCR ceramic material and their weight parts are: 100 parts of PTCR ceramic granulated powder, 0.3 parts of alumina whiskers, 0.3 parts of tetrabutyl titanate and 0.5 parts of glycerol;
[0071] The PTCR ceramic granulation powder has a Tc temperature of 235°C, a powder particle size of 5μm-100μm, a moisture content of 0.16%, and includes polyvinyl alcohol accounting for 0.75% by mass.
[0072] Comparative Example 4 (Tc235-0-1)
[0073] The method is basically the same as Example 5, except that: the raw material components of the toughened PTCR ceramic material and their weight parts are: 100 parts of PTCR ceramic granulated powder, 0 parts of alumina whiskers, 0.15 parts of tetrabutyl titanate and 0.25 parts of glycerol;
[0074] The PTCR ceramic granulation powder has a Tc temperature of 235°C, a powder particle size of 5μm-100μm, a moisture content of 0.16%, and includes polyvinyl alcohol accounting for 0.75% by mass.
[0075] Comparative Example 5 (Tc235-0-2)
[0076] The method is basically the same as Example 5, except that: the raw material components of the toughened PTCR ceramic material and their weight parts are: 100 parts of PTCR ceramic granulated powder, 0.15 parts of alumina whiskers, 0 parts of tetrabutyl titanate and 0.25 parts of glycerol;
[0077] The PTCR ceramic granulation powder has a Tc temperature of 235°C, a powder particle size of 5μm-100μm, a moisture content of 0.16%, and includes polyvinyl alcohol accounting for 0.75% by mass.
[0078] Comparative Example 6 (Tc235-0-3)
[0079] The method is basically the same as Example 5, except that: the raw material components of the toughened PTCR ceramic material and their weight parts are: 100 parts of PTCR ceramic granulated powder, 0.15 parts of alumina whiskers, 0.15 parts of tetrabutyl titanate and 0 parts of glycerol;
[0080] The PTCR ceramic granulation powder has a Tc temperature of 235°C, a powder particle size of 5μm-100μm, a moisture content of 0.16%, and includes polyvinyl alcohol accounting for 0.75% by mass.
[0081] Test Example 1
[0082] The Tc185-15 of Example 2 was characterized, and the results were as follows Figure 1 As shown. Figure 1It can be seen that some whiskers are unevenly distributed in the PTC ceramic grains, and are clearly separated from the ceramic body material. Its main component is aluminum oxide, indicating that the whiskers are aluminum oxide whiskers. The diameter of the whiskers is about 1μm, and the length varies from 10μm to 20μm. This shows that the added aluminum oxide whiskers do not react with the ceramic body material, and still exist in the material matrix as a second item after high-temperature sintering. This shows that the presence of aluminum oxide whiskers can increase the mechanical strength of the ceramic material, and this enhancement effect can be clearly seen from the subsequent performance test results.
[0083] Test Example 2
[0084] After the toughened PTCR ceramic materials of Examples 1-6 and Comparative Examples 1-6 were metallized (upper electrode), resistance-temperature and other characteristics were measured;
[0085] Room temperature resistance (R25): Use a multimeter to test its resistance value in an environment of 25±2℃;
[0086] Curie temperature (Tc): Place the PTC sample in a resistance furnace, heat it up at a rate of 2°C / min-5°C / min, and record the resistance of the sample at different temperatures (RT curve); the test temperature range is: room temperature about 330°C; find the minimum resistance value (R min ) temperature (T min ), when the resistance value increases to (2×R min ) is the Curie temperature Tc (Tc>T min );
[0087] Rise-to-Resistance Ratio: The logarithm of the ratio of the maximum resistance to the minimum resistance on the RT curve, i.e. log(R max / R min ), R max is the maximum resistance value on the RT curve;
[0088] Temperature coefficient (α15): a parameter that describes how fast resistance changes with temperature, and is an important characteristic of the PTC effect; its calculation formula is: α15 = 2.303*log(R2 / R1) / (T2-T1), where T2 = Tc+15, T1 = Tc, and R2 and R1 correspond to the resistance values at temperatures T2 and T1, respectively;
[0089] Breakdown voltage (Vbd): Apply voltage to the PTC sample at a boost rate of 50 VDC / min until breakdown occurs, and record the voltage value before breakdown, which is the breakdown voltage Vbd.
[0090] Flexural strength (N): The flexural strength was tested using the three-point method. The PTC sample was placed horizontally on two cylindrical support rods 15 mm apart, with the sample length direction perpendicular to the length direction of the cylinder. A 2.0 mm diameter steel indenter was used to press down at a speed of 5 mm / min at the center of the two support rods above the PTC, and the pressure at the breakdown was recorded.
[0091] Figure 2 The resistance-temperature characteristic comparison curve of Tc235-15 of Example 5 and Tc235-0-1 of Comparative Example 4;
[0092] Table 1 shows the relevant test results:
[0093] Table 1
[0094]
[0095]
[0096] From Table 1 and Figure 2 It can be seen that the toughened PTCR ceramic material of the embodiment exhibits excellent PTC effect and mechanical properties.
[0097] It can be seen from Examples 1-3 and Comparative Example 1 that after adding alumina whiskers, tetrabutyl titanate and glycerol, the Curie temperature, lift-to-resistance ratio and temperature coefficient of the Tc185 material did not change much and were within the controllable range. In particular, under the condition of similar room temperature resistance, the withstand voltage strength of the material did not change significantly, indicating that alumina whiskers, tetrabutyl titanate and glycerol did not cause significant deterioration of the electrical properties of the PTCR material. However, after the improvement, the flexural strength of the toughened PTCR ceramic material increased significantly.
[0098] It can also be seen from Example 2 and Comparative Examples 2-3 that the average flexural strength of the aluminum oxide whiskers is also high when glycerol or tetrabutyl titanate is not added, but the difference between individuals is about 20%, indicating that the aluminum oxide whiskers are unevenly distributed in the material, resulting in large differences in flexural strength. The dispersibility effect of tetrabutyl titanate and glycerol on aluminum oxide whiskers can be clearly reflected in this comparative example.
[0099] It can be seen from Examples 4-6 and Comparative Example 4 that after adding alumina whiskers, tetrabutyl titanate and glycerol, the Curie temperature of the Tc235 material increased, the lift-to-drag ratio decreased to a certain extent, and the temperature coefficient did not change much, all of which were within the allowable variation range. However, the withstand voltage of the material with a high addition amount decreased, indicating that the addition amount of alumina whiskers in this series of materials should not be too high. However, after the improvement, the flexural strength of the toughened PTCR ceramic material increased significantly.
[0100] Similarly, it can be seen from Example 5 and Comparative Examples 5-6 that the average flexural strength of the aluminum oxide whiskers added without glycerol or tetrabutyl titanate is also high, but the difference between individuals is more than 20%, indicating that the aluminum oxide whiskers are unevenly distributed in the material, resulting in large differences in flexural strength. The dispersibility effect of tetrabutyl titanate and glycerol on aluminum oxide whiskers can also be clearly reflected in this comparative example.
[0101] Obviously, the above embodiments are merely examples for clear explanation and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.
Claims
1. A toughened PTCR ceramic material, characterized in that: The raw material components of the toughened PTCR ceramic material and their weight parts are: 100 parts of PTCR ceramic granulated powder, 0.03-3 parts of alumina whiskers, 0.03-3 parts of tetrabutyl titanate and 0.05-5 parts of glycerol.
2. The toughened PTCR ceramic material according to claim 1, characterized in that: The Tc temperature of the PTCR ceramic granulated powder is 120° C.-290° C., the particle size of the powder is 5 μm-100 μm, and the moisture content is 0.05%-0.3%.
3. The toughened PTCR ceramic material according to claim 1, characterized in that: The PTCR ceramic granulated powder also includes polyvinyl alcohol in an amount of 0.3% to 1.2% by weight.
4. The toughened PTCR ceramic material according to claim 1, characterized in that: The diameter of the aluminum oxide whisker is 0.1 μm-5 μm, and the length is 5 μm-100 μm.
5. The toughened PTCR ceramic material according to claim 1, characterized in that: The purity of the aluminum oxide whisker is above 99.5%.
6. The toughened PTCR ceramic material according to claim 1, characterized in that: The mass ratio of the aluminum oxide whisker, tetrabutyl titanate and glycerol is 3:5:
5.
7. The method for preparing a toughened PTCR ceramic material according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1, dispersing alumina whiskers, tetrabutyl titanate and glycerol uniformly, and then adding PTCR ceramic granulation powder and mixing uniformly to obtain a mixed material; S2. Dry-pressing and sintering the mixed material described in S1 to obtain the toughened PTCR ceramic material.
8. The method for preparing the toughened PTCR ceramic material according to claim 7, characterized in that: In S1, the uniform dispersion time is 15 min-30 min.
9. The method for preparing the toughened PTCR ceramic material according to claim 7, characterized in that: In S1, the uniform mixing speed is 55 rpm-65 rpm, and the time is 0.1 h-8 h.
10. The method for preparing the toughened PTCR ceramic material according to claim 7, characterized in that: In S2, the sintering temperature is 1250°C-1350°C, the time is 0.1h-1h, the atmosphere is air atmosphere, and the pressure is normal pressure.